Polar-Coded Modulation - Seidl, Mathis; Schenk, Andreas; Stierstorfer, Clemens; Huber, Johannes B. (IEEE transactions on communications, 2013)
A framework is proposed that allows for a joint description and optimization of both binary polar coding and 2 m -ary digital pulse-amplitude modulation (PAM) schemes. For the latter, the multilevel coding (MLC) approach as well as bit-interleaved coded modulation (BICM) are considered. The conceptual equivalence of polar coding and multilevel coding is covered in detail. Based on an alternative characterization of the channel polarization phenomenon, rules for the optimum choice of the labeling in coded modulation schemes employing polar codes are developed. Simulation results regarding the error performance of the proposed schemes on the AWGN channel are included.